Onym Derivatives in Mining Terminology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The paper investigates the appellative onym derivatives that function in the Mining terminology. It also focuses on the derivative-genetic connections. The nominations of rocks and minerals become the basis of tracing the methods of word formation (morphological and non-morphological). Furthermore these language units allow distinguishing the most productive formants, such as the suffixes -ит, -іт, and -літ. Moreover this research studies the certain problems of the derivative base formation, its semantics and some of the phono-morphological processes, which accompany the process of word formation (alternation, truncation, interfixation). It is observed that the typical way for specific Mining term production is interfixation. It is defined as a morphological phenomenon, in which an asemantic gasket appears on a morphemic seam. Intermorphemic segments generally fulfill a formal function. Their task is to simplify the process of combining morphemes. The most commonly reduced language units are one-component finite segments, consisting of a vowel phoneme or phonemic combinations.The paper reveals the peculiarities of adaptation and codification of distinctive Ukrainian nominations, their variability, as well as explains the reasons for its formation. The emphasis is laid on the inconsistency and contradictions in the production and spelling of appellative onym derivatives, which sometimes occurs contradicting the current principles of the Ukrainian language (orphoetic, spelling, word formation, etc.). Firstly, the variation of spelling the Latin letters g and h in the Ukrainian language is distinguished. Secondly onym derivatives that are produced on the basis of their own nominations and illustrate doubling are analyzed. Thirdly onym derivatives and appellate derivatives associated with the so-called “nine” rule are investigated. The usage of foreign language letters and letter combinations denoting sounds, which are not specific to the Ukrainian language are represented.The lack of research studying the problems of standardization and unification of Mining terminology leads to the emergence of so-called double standards. Moreover, such double standards are represented by lexicographic works and give the right to choose sometimes correct substitutes.
Keywords: mining terminology; onym derivate; onym derivative; formant; suffix; phonomorphological processes; spelling